ENT600: J.E.M Company smart fogger blue print / Mohd Subky Ismail, Edzatul Noradiah Durimi and Jessica Joseph - Ismail, Mohd Subky; Durimi, Edzatul Noradiah; Joseph, Jessica (2018)
J.E.M Company is a business provides technology development on fogging machine. This product was develop after doing a lot of survey, research and observations and the main purpose is to enhance the existing fogging machine function, reduce the difficulty and ergonomic disease among user. After some evaluation and discussion, SMART FOGGER is more convenient and might solve current situation. Our current main target buyer is to Ministry Of Health, Inspectorate Health District, Vector Unit Control. We are taking into consideration to expand our target among private sector, pest control and agricultural in future. There are 3 of us running these partnership businesses which carry each responsibility according to each speciality.